Correlation analysis of mechanical and state characteristics of diesel engine exhaust particles. Issue 6 (21st April 2022) - Liu, Shuai; Zhang, Libin; Wang, Zhong
Abstract: Aiming at the influence of diesel engine exhaust particle mechanical characteristics on the state characteristics, studies were carried out using atomic force microscopy, high‐resolution transmission electron microscopy, and x‐ray small‐angle scattering. The variation rules of cluster‐particle interaction force and state characteristic parameters such as particle morphology and spatial structure were discussed. According to the principle of normalization, the relationship between the mechanical and state characteristics of the particles is analyzed. The results show that as the particle size increases in the exhaust process, the attractive force F at, adhesion F ad, and adhesion energy W ad increase between the particles, F at from 1.27 to 1.58 nN, F ad from 3.75 to 4.38 nN, W ad from 2.17 × 10 −16 to 2.44 × 10 −16  J. The particles are gradually agglomerated, and the cluster size is increased, indicating a certain relationship between the mechanical characteristics of the particles and the morphology. Along the exhaust direction, the particle equivalent diameter increases, and the mechanical characteristics are enhanced, while the organic matter and moisture in the exhaust are continuously adsorbed, aggravating the aggregation and shrinkage between the particles. The scattering characteristic parameters q min and q T decrease, q min from 0.34 to 0.28 and q T from 0.72 to 0.63, the pore structure parameters decrease, the pore number concentration decreases, the peak pore size changes from 7–9 nm to 5–6 nm, the agglomerate particle structure defects decrease and the density is increased, indicating that there is a certain relationship between the mechanical characteristics of the particles and the spatial structure.